(untitled) (Universal International Scientific Journal, 2026)
This thesis substantiates the didactic and psychological potential of digital innovations in developing students’ communication skills in educational lessons. As an innovation, criteria and assessment indicators for integrating digital communication tasks with educational goals are proposed.